Edukasi Metode Peer Group tentang HIV/AIDS terhadap Pengetahuan dan Perilaku Seksual Remaja - Dewi Sartiya Rini; Sitti Muhsinah; Rusna Tahir (JURNAL KESEHATAN PRIMER, 2022)
Background: Several big cities in Indonesia stated that almost 50% of teenagers had premarital sex. And what is most astonishing is the widespread circulation of sex videos of teenagers wearing school uniforms on the internet. This phenomenon is motivated by the nature of adolescents who tend to want to try all things that are new and challenging. The high presentation of risky behaviour by adolescents needs to be a serious concern for all groups, considering that the transmission of HIV AIDS occurs mainly through sexual intercourse. This study was to see the effect of peer group education on HIV/AIDS on the knowledge and sexual behaviour of adolescents at SMAN 10 Kendari. Methods: This study used a quasi-experimental design with a pre-post test with a control group approach with 60 respondents. Results: There was a significant difference between the mean knowledge scores of the control and intervention groups before and after the intervention with p-value = 0.006, and adolescent sexual behaviour also showed effective results with p-value = 0.046. Conclusion: The peer education method affects knowledge and sexual behaviour, so this method can be used to educate adolescents so that the flow of information delivery is better.